2023
DOI: 10.1503/jpn.220086
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfield alterations in schizophrenia and major depressive disorder: a systematic review and network meta-analysis of anatomic MRI studies

Abstract: Background: Hippocampal disturbances are important in the pathophysiology of both schizophrenia and major depressive disorder (MDD). Imaging studies have shown selective volume deficits across hippocampal subfields in both disorders. We aimed to investigate whether these volumetric alterations in hippocampal subfields are shared or divergent across disorders. Methods: We searched PubMed and Embase from database inception to May 8, 2021. We identified MRI studies in patients with schizophrenia, MDD or both, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 93 publications
1
14
1
Order By: Relevance
“…However, increases in left CA3, CA4, and GC.ML.DG volumes from baseline to 5-week follow up trended toward significance, suggesting possible longer-term effects of ketamine on hippocampal structure. Finally, consistent with prior findings in the field suggested that depression was associated with smaller hippocampal volume ( 42 , 43 ), we found that patients with TRD relative to HC had smaller left CA4 and GC.ML.DG baseline volumes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, increases in left CA3, CA4, and GC.ML.DG volumes from baseline to 5-week follow up trended toward significance, suggesting possible longer-term effects of ketamine on hippocampal structure. Finally, consistent with prior findings in the field suggested that depression was associated with smaller hippocampal volume ( 42 , 43 ), we found that patients with TRD relative to HC had smaller left CA4 and GC.ML.DG baseline volumes.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that patients with TRD had significantly smaller pre-treatment volumes in the left CA4 and GC.ML.DG when compared to HC. Reduced volumes of CA1 ( 43 , 46 ), CA3 ( 42 , 43 , 46 ), CA4 ( 42 , 43 ), and GC.ML.DG ( 42 ), have been reported in patients with MDD when compared to healthy controls, although the laterality of reports vary. There are several theories that speculate about the underlying biological mechanism driving reduced hippocampal volume observed in patients with depression ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of amygdala subfield volumes in MDD suggest that the lateral and anterior amygdaloid areas are smaller in individuals with MDD compared to HCs (individuals with SAD=147; HCs=144) 64 , whilst other studies report null findings (patient=76; HC=77) 65 . The present findings of larger hippocampal subfield volumes further contrast with recent meta-analyses which suggest that MDD is associated with smaller hippocampal CA3, CA4 and larger HATA volumes, compared to HCs 23 . The fact that only the AB remained significant suggests that major depression comorbidity may have an influence on subfield volumes in SAD.…”
Section: Discussioncontrasting
confidence: 99%
“…Given the roles of the amygdala and hippocampus in fear and anxiety 20,21 , and developments in amygdala and hippocampal segmentation techniques (Saygin et al, 2017), there have been increasing reports of subfield volume alterations in anxiety-related disorders 22 . Reviews of the hippocampal subfields literature suggest that individuals with MDD have smaller volumes of the CA3/4 and larger volume of the hippocampus–amygdala transition area (HATA) compared to HCs 23 , while individuals with PTSD have smaller volumes of the CA1/3 and dentate gyrus (DG) compared to HCs (Ben-Zion et al, 2023). Moreover, Koch and colleagues (2021) found that a smaller dentate gyrus volume prospectively predicted PTSD vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological abnormalities in the hippocampus have been extensively investigated in relation to MDD ( Belleau et al, 2019 ). A study conducted a comparative analysis of Magnetic Resonance Imaging (MRI) results between MDD patients and a healthy control group, unveiling a reduction in the volume of the left hippocampal CA3 and CA4 regions, alongside an elevation in the volume of the right hippocampal amygdala transition area (HATA) ( Sun et al, 2023 ). Another report identified hippocampal atrophy in MDD patients experiencing anhedonia, specifically in the left CA1 and DG subfields, which may be associated with the lack of pleasure endemic to MDD ( Wu et al, 2023 ).…”
Section: Pathological Connection Between Ahn and Mddmentioning
confidence: 99%